Ultrahigh-Speed In-Memory Electronics Enabled by Proximity-Oxidation-Evolved Metal Oxide Redox Transistors - Kumar, Mohit; Kim, Unjeong; Lee, Wang Gon; Seo, Hyungtak (Advanced Materials, 2022)
The pursuit of a universal device that combines nonvolatile multilevel storage, ultrafast writing/erasing speed, nondestructive readout, and embedded processing with low power consumption demands the development of innovative architectures. Although thin-film transistors and redox-based resistive-switching devices have independently been proven to be ideal building blocks for data processing and storage, it is still difficult to achieve both well-controlled multilevel memory and high-precision ultrafast processing in a single unit, even though this is essential for the large-scale hardware implementation of in-memory computing. In this work, an ultrafast (≈42 ns) and programable redox thin-film transistor (ReTFT) memory made of a proximity-oxidation-grown TiO2 layer is developed, which has on/off ratio of 105, nonvolatile multilevel analog storage with a long retention time, strong durability, and high reliability. Utilizing the proof-of-concept ReTFTs, circuits capable of performing fundamental NOT, AND, and OR operations with reconfigurable logic-in-memory processing are developed. Further, on-demand signal memory-processing operations, like multi-terminal addressable memory, learning, pattern recognition, and classification, are explored for prospective application in neuromorphic hardware. This device, which operates on a fundamentally different mechanism, presents an alternate solution to the problems associated with the creation of high-performing in-memory processing technology.
Keywords: In-memory processing; Metal-oxide; Multi terminals; Multilevel storage; Nonvolatile; Proximity oxidation; Ultra high speed; Ultra-fast; Ultrafast memory; Ultrathin layers; in-memory processing; multi-terminals; proximity oxidation; ultrafast memory; ultrathin layers